2010
DOI: 10.1111/j.1463-1318.2009.01831.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial of the influence of local subcutaneous infiltration vs subcutaneous and deep infiltration of local anaesthetic on pain after appendicectomy

Abstract: Both methods of administration of local anaesthetic produced consistently low pain scores in the first 24 h after appendicectomy. There may be additional benefit in a local nerve field blockade in combination with local anaesthetic skin infiltration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…Our study results has been favored by some studies while other studies concluded that infiltration of bupivacaine before incision (pre-emptive) provided better postoperative analgesia than infiltration near closure of wound ( preventive). J K Randall et al found no significant difference in mean pain scores between pre and post incision infiltration of bupivacaine at 1 st , 4 th and 8 th hour post appendectomy similar to our study 11 .…”
Section: Discussionsupporting
confidence: 89%
“…Our study results has been favored by some studies while other studies concluded that infiltration of bupivacaine before incision (pre-emptive) provided better postoperative analgesia than infiltration near closure of wound ( preventive). J K Randall et al found no significant difference in mean pain scores between pre and post incision infiltration of bupivacaine at 1 st , 4 th and 8 th hour post appendectomy similar to our study 11 .…”
Section: Discussionsupporting
confidence: 89%
“…Preoperative local wound infiltration into the skin and deep to the external oblique during open appendicectomy showed a relevant reduction in pain intensity; this, together with little to no side effects, enabled its recommendation for open appendicectomies 89,90,93 . Because of a lack of studies on wound infiltration in laparoscopic approaches, there was no evidence to formulate recommendations for this type of surgical procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Seven studies investigated the effect of local wound infiltration, including 532 patients: one study for single-incision laparoscopic appendicectomy in adults; 87 three studies for open appendicectomy in adults, [88][89][90] two studies for open appendicectomy in children 91,92 and one study concerning open appendicectomies in a mixed population. 93…”
Section: Wound Infiltrationmentioning
confidence: 99%
See 2 more Smart Citations